2005
DOI: 10.1534/genetics.104.032805
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Scan for Anal Atresia in Swine Identifies Linkage and Association With a Chromosome Region onSus scrofaChromosome 1

Abstract: Anal atresia is a rare and severe disorder in swine occurring with an incidence of 0.1-1.0%. A wholegenome scan based on affected half-sibs was performed to identify susceptibility loci for anal atresia. The analysis included 27 families with a total of 95 animals and 65 affected piglets among them. Animals were genotyped for 126 microsatellite markers distributed across the 18 autosomal porcine chromosomes and the X chromosome, covering an estimated 2080 cM. Single-point and multipoint nonparametric linkage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
4
5
0
1
Order By: Relevance
“…Figure 1 and 2 shows the profiles of the multipoint NPL scores and the respective information content (Info) for each chromosome. The average information content was 0.52, which is a similar value to those found in previous studies in swine [ 16 ] and humans [ 17 ]. Two chromosomal regions had linkage score exceeding the nominal significance level of p < 0.001.…”
Section: Resultssupporting
confidence: 87%
“…Figure 1 and 2 shows the profiles of the multipoint NPL scores and the respective information content (Info) for each chromosome. The average information content was 0.52, which is a similar value to those found in previous studies in swine [ 16 ] and humans [ 17 ]. Two chromosomal regions had linkage score exceeding the nominal significance level of p < 0.001.…”
Section: Resultssupporting
confidence: 87%
“…As in other studies [7,9], we found distinct linkage results between TDT and NPL [5]. NPL test for markers linked to genes affecting disease status on the basis of identity-by-descent, and is more powerful when the marker density is low.…”
Section: Discussionsupporting
confidence: 81%
“…[42][43][44][45] Atresia ani is believed to be inherited in cattle and pigs. 46,47 In camelids, most intestinal malformations are thought to be heritable, although true data are lacking; atresia ani has been reported anecdotally in related llamas. Some cases may also be sporadic and arise from random mutations or unidentified environmental influences; rectal palpation is not commonly Prior to attempting surgical correction, it is important to discuss the possibility of atresia coli being heritable and that the animal should probably not be used for breeding.…”
Section: Congenital Defectsmentioning
confidence: 99%